Changthangi : The pride of Jammu and Kashmir - Shanaz, Syed; Firdous, Firdous; Alam, Safer; Nusrat, Nusrat (Indian Farming, 2020)
Changthangi is a well-recognized breed of goat popular for its valuable produce called pashmina. The breeding tract of this goat is in the Changthang area of Leh district of Jammu and Kashmir and is adjacent to Tibet. The breed is well adapted to the local cold arid agro-climatic conditions of the region and is reared mainly by a nomad known as ‘Changpa’. The fibre produced by this breed is the prime source for the world-class shawl industry of Kashmir. In addition to pashmina, this goat is also reared for chevon, milk, manure, pelt and even carriage. The number of this goat is presently declining and restricted mainly to Changthang area. Changthang region has harsh climatic dryness (with very low rainfall) and temperature varies from – 40°C to +40°C. The majority of the animals have white coat, though brownish red, fawn, grey and black animals are also seen. The horns are brown and mostly curved in shape. The Changthangi goats are small in body size (adult’s body weight 26.50-30 kg). The major breeding season is July-November, while main kidding season at high altitude is February to April. The most prevalent diseases in the area are CCPP, PPR, EMD, goat pox and foot rot. The breed has high economic importance and market for the livelihood of the breeders.